Profile of Scientific Literacy Ability of Middle School IPA (Natural Sciences) Teachers in Banda Aceh City - Muhammad Azzarkasyi; Syamsul Rizal; Risaharti Risaharti (International Conference on Multidisciplinary Research, 2022)
This study aims to obtain a description of the scientific literacy ability of IPA (natural sciences) teachers. This study is descriptive research. Data was collected by distributing diagnostic test instruments distributed to 29 teachers who were selected as a sample of the total population of science teachers teaching at SMPN (public junior high school) throughout Banda Aceh. The test instrument used in the form of Four-Tier Multiple Choice questions as many as 24 items equipped with CRI confidence level scale along with the reasons for the answer choices. The scientific literacy competency aspect used is in accordance with the 2017 PISA determination which includes 3 aspects, namely the competence aspect to explain phenomena scientifically, the competence aspect to design and evaluate scientific investigations, and the competence aspect to interpret data and evidence scientifically. The results showed that the scientific literacy ability of science teachers at SMPN in Banda Aceh was in the medium category with a percentage of 48.48%. The ability based on competence to explain phenomena scientifically is in the medium category with a percentage of 46.55%, the competence to design and evaluate scientific investigations is in the medium category with a percentage of 61.64% and the competence to interpret data and evidence scientifically is in the medium category as well with a percentage of 37.24%. Based on the results of this study, it can be concluded that science teachers at public junior high schools in Banda Aceh have moderate scientific literacy skills. Keywords: profile, scientific literacy, science teacher